The Social and Legal Context of Electronic Crime: A Comparative Study between Algerian and Jordanian Legislation - Mustapha, Malika Hadjadj; AbuAnzeh, Amal (Dirasat: Human and Social Sciences, 2023)
Objectives: The study presents the effects of electronic crime on society when perpetrators exploit electronic media in an attempt to satisfy their aspirations. This study deals with the criminal policy used to confront these crimes and deter their perpetrators by defining their definition and elements, and the penalties prescribed for their perpetrators in Algerian legislation compared to Jordanian legislation. Methods: The study applied the comparative legal approach, by presenting the legal texts regulating electronic crime, clarifying the terms and conditions that they contain, analyzing and commenting on them, as well as comparing the Jordanian and Algerian legislation approach in the face of electronic crime, describe the strengths and weaknesses of each. Results: The study reached the awareness of Jordanian and Algerian legislators of the danger of electronic crime on society and their efforts to amend their legal texts. However, the Algerian legislator did not deal with the crime of electronic forgery , whether in the Penal Code or in any special law. Also, the penalties stipulated in the Algerian and Jordanian legislation are not commensurate with the gravity of electronic crime, which may not achieve the main objectives of the penalty with public and private deterrence. Conclusions: The study concluded that the text of the Algerian Penal Code regulating the crime of forgery should be amended to apply to electronic forgery and the need to reconsider the penalties stipulated in the Algerian and Jordanian legislation for electronic crime perpetrators and the aggravating circumstances thereof.